A review of electrical discharge machining on various superalloys. (2022) - Kunal,; Sudhakar Rao, P.; Yunus Khan, Mohd.; Saidaiah, K.
Highlights: This work presents review of the work done in the field of the EDM machining in the recent past, basically deals with the EDM machining of Superalloys. Study of various parameters during the machining. The effect of dielectric fluids during the machining was observed. Research gaps were observed, materials still to be explored for the parameters research during EDM machining. The conclusions of this investigation were found to be consistent with available literature. Abstract: Superalloys are a group of nickel, iron–nickel and cobalt alloys used in various applications. These metals have excellent heat resistant properties and retain their stiffness, strength, toughness and dimensional stability at temperatures much higher than the other aerospace structural materials hence are also known as metal of future. This paper reviews the EDM machining superalloys like Nickel-based superalloys, Cobalt-based superalloys, iron based superalloy also the effect of parameters on MRR, EWR, and surface roughness. The study suggest that current and pulse on time were the most influential parameters, current below 1 A with changing polarity are more effective. Polarity also plays an important role in deciding MRR.